Chronic hepatitis B infection and the risk of gestational diabetes: a cross‐sectional study. (15th April 2020) - Giles, ML; Davey, M‐A; Wallace, EM
Abstract : Objective: An estimated two billion people worldwide live with hepatitis B virus (HBV) infection. Many of these are women of reproductive age. Studies that have examined pregnancy outcomes in women living with HBV have reported conflicting results in relation to the incidence of gestational diabetes (GDM). The aim of this study is to examine if gestational diabetes is more common in women with chronic HBV residing in a non‐Asian country. Design: Cross‐sectional study. Setting: Victoria, Australia. Population: All singleton births between 2009 and 2017. Methods: Poisson regression was performed to determine whether gestational diabetes is more common in women with HBV than in women without HBV taking into account other risk factors such as maternal age, body mass index (BMI), parity and country of birth. Main outcome measure: Gestational diabetes diagnosis in women with chronic HBV infection. Results: For women with HBV, the unadjusted incidence risk ratio for GDM was 1.75 (95% CI 1.6–1.9). After adjusting for region of birth, BMI, parity, age and smoking, the adjusted incidence risk ratio was 1.2 (95% CI 1.1–1.3). The highest incidence (37.1%) of GDM was in women with HBV and a BMI of >40. Conclusions: The findings from this study confirm an association between HBV and GDM. Tweetable abstract: HBV is associated with GDM with an incidence risk ratio for GDM of 1.75 (95% CI 1.6–1.9). Tweetable abstract: HBV is associated with GDM with an incidence risk ratio for GDM of 1.75 (95% CI 1.6–1.9).